ICRF - volume charge - antenna edge interactions in the torsatrons U-3M and U-2M Part 2. VSC - RF antenna interaction - Berezhnyj, V.L. (Вопросы атомной науки и техники, 2016)
The influence of the electron emission and metal impurity emission from the antennas, including the U-3 torsatron antenna, on the RF-discharge has been analyzed. The both effects are the results of the antenna surface bombarding with ions being accelerated in the self-consistent field of the volume-space charge (VSC).